The master hat - Cheah, Pike See; Othman, Fauziah; Bala, Usman; Wong, Jyen Yiee; Ling, King Hwa (Universiti Putra Malaysia Press, 2016)
Are your left brain and right brain the same? No! The two halves of your brain may look similar, but they are not exactly alike. The two halves, known as hemispheres, have functional specialization whereby there is a preference to use one brain region more than others for specific functions. Brain lateralization refers to how some brain functions tend to localize primarily in one half of the brain.